2011
DOI: 10.1007/s10803-011-1366-y
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: An Exploratory Study of Lexical Skills in Bilingual Children with Autism Spectrum Disorder

Abstract: Studying lexical diversity in bilingual children with autism spectrum disorders (ASD) can contribute important information to our understanding of language development in this diverse population. In this exploratory study, lexical comprehension and production and overall language skills were investigated in 14 English-Chinese bilingual and 14 English monolingual preschool-age children with ASD. Results indicated that both groups had equivalent scores on all but one measure of language and vocabulary, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(107 citation statements)
references
References 13 publications
4
101
1
1
Order By: Relevance
“…Other studies investigating language aspects of autistic children in bilingual [20][21][22][23], multicultural environments [24,25], speciically with minority groups [26], of immigrants [27] reported aspects like those observed in this study. One study [10] was found that involved research into autism awareness and knowledge about autism speciically in foreigners.…”
Section: Discussionsupporting
confidence: 81%
“…Other studies investigating language aspects of autistic children in bilingual [20][21][22][23], multicultural environments [24,25], speciically with minority groups [26], of immigrants [27] reported aspects like those observed in this study. One study [10] was found that involved research into autism awareness and knowledge about autism speciically in foreigners.…”
Section: Discussionsupporting
confidence: 81%
“…The same phenomenon of more children with ASD having migrant parents was observed in a population study of 208 registered cases with ASD performed in Stockholm a few years ago (Fernell et al, 2010). Recent studies suggest that bilingual exposure is not correlated to language delay in children with ASD (Hambly & Fombonne, 2012;Petersen, Marinova-Todd, & Mirenda, 2012). In accordance with these studies, we found no significant differences as regards language levels in our cohort between the children whose two parents were Swedish native speakers and those who had at least one parent speaking another mother tongue.…”
Section: Discussionmentioning
confidence: 52%
“…21 Other studies of preschool age children with ASD found that bilingually-exposed children did not experience additional delays in language development, but these studies did not specifically examine EF. 22,23 One study of children with autism further subdivided the bilingual group based on simultaneous (i.e., exposure from birth) versus sequential (i.e., after one year of age) exposure; the only difference was stronger parent-rated social interaction scores for the simultaneous compared to sequential exposure group. 22 …”
mentioning
confidence: 99%